Implementation of Criminal Law Provisions Against Serial Murders in Indonesia - Pepa, Cindy Oktaviany (Universitas Negeri Gorontalo, 2022)
This study analyzes the implementation of criminal law provisions and sentencing for serial killers in Indonesia, addressing critical gaps in the existing legal framework. Applying a normative legal research approach—employing statute, conceptual, and case analyses—the study identifies two key issues. First, Indonesian courts predominantly rely on Article 340 of the Criminal Code, which pertains to premeditated murder, owing to the absence of specific provisions for serial murders. This reliance induces inconsistencies in sentencing, as serial murders, owing to their unique characteristics, do not neatly align with existing legal definitions. Second, the study highlights the lack of explicit guidelines in the Criminal Code regarding the classification of serial murder and the minimum punishment for such crimes. Judges typically apply Article 340 in conjunction with other relevant articles. However, because of the absence of a standardized framework for determining the severity of serial murders, sentences vary, often leading to unjust outcomes. This study underscores the urgent need for legislative reforms in Indonesia to address these gaps, proposing the development of specific legal provisions for serial murders. By defining serial murder more accurately and setting unambiguous sentencing parameters, the law could ensure more consistent and just rulings. This study contributes to the ongoing discourse on criminal law reform in Indonesia, emphasizing the importance of adapting legal frameworks to better address emerging and complex criminal behaviors such as serial murder. The findings necessitate immediate attention to legal clarity and consistency in adjudicating severe crimes.